Investigating immersion and presence in virtual reality for architectural visualization - Azmi, Athira; Syed Mohamad, Sharifah Mashita (Science and Information Organization, 2025)
The architecture industry increasingly relies on virtual reality (VR) for architectural visualization, yet there is a critical issue of insufficient user involvement in the design process. This study investigates the sense of immersion and presence in the virtual environment among 60 Malaysian participants aged 20 to 40. The study utilized a 1000 sq. ft. apartment with three bedrooms and two bathrooms, was replicated in a 3D model based on real-world references. Our findings show that participants were moderately immersed in the virtual environment (M = 4.86), but the lack of sense of touch, lack of detail, and interactivity within the virtual environment affected their sense of immersion in VR for architectural visualization. This study has enhanced our understanding of human-computer interaction in VR, specifically for architectural visualization, and has emphasized the importance of improving these aspects to create more effective architectural visualization user experiences.